Análise Cienciométrica das produções científicas do Encontro Nacional de Pesquisa em Ensino em Ciências (ENPEC) sobre o tema Educação alimentar, tendências e lacunas - FIGUEIRA, Rodrigo Leonardo da Silva (2023)
The food and nutrition issue is essential for the search for a better quality of life and health promotion. The performance of good dietary practices contributes to the prevention of various pathologies and helps our body to have a balance for the optimal functioning of our body. This study aimed to analyze the scientific productions on food and nutrition education in the Proceedings of the National Meeting of Research in Science Education (ENPEC) from 2011 to 2019. The qualitative research used scientométrics. The research corpus consists of 214 articles collected in the thematic line health education and science education. Data analysis addresses the following aspects: distribution of articles by years, number of articles by region, institutions, classification regarding the nature of academic productions, the approach, methodologies, types of instruments used by academic productions, and locus of academic productions. The participation of higher education institutions in the North and Northeast regions has little significance in relation to the South and Southeast regions, this is due to the location where the events occur most, in the Southeast. Regarding the methodologies that stand out are applied research, it shows the researcher going to the field of collection, with the scenario of its occurrence being the school space. We evidence that the number of scientific productions about nutritional education is little explored in relation to the total number of productions throughout the analyzed period. Thus, it is necessary that educational institutions encourage further research with a focus on this theme and others related to the issue of food health.